Impact of Teaching Practicum Experiences on The Development of Cultural Sensitivity in Pre-Service EFL Teachers in Indonesia - Putri, Aliffia Ganish Herliana; Widagsa, Rudha (Universitas PGRI Yogyakarta, 2025)
This study explores the influence of teaching practice experiences on pre-service English as a Foreign Language (EFL) teachers' cultural sensitivity, specifically their sensitivity to school culture, and examines how this cultural sensitivity impacts their teacher identity formation. Employing a qualitative case study approach, the research involved interviews with three pre-service EFL teachers. Thematic analysis was used to interpret the data, revealing several key findings. The study found that teaching practice significantly enhanced pre-service EFL teachers' awareness of school culture, encompassing the distinct academic environment and customs encountered in schools compared to their campus experiences. Additionally, this experience improved their classroom management, selection of teaching methods, and fostered greater patience and confidence in their teaching roles. Moreover, increased cultural sensitivity positively influenced the development of their professional identities, highlighting the importance of emotional factors such as a sense of belonging to the teaching profession, preparedness for the classroom, and self-assurance. Overall, the study underscores that teaching practice not only deepens pre-service teachers' understanding of school culture but also equips them emotionally and professionally for their future careers.